1997
DOI: 10.3758/bf03205517
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of head motion cues to localization of low-pass noise

Abstract: Localization of low-pass sounds was tested in relation to aspects of Wallach's(1939Wallach's( , 1940 hypotheses about the role of head movement in frontJback and elevation discrimination. With a 3-sec signal, free movement of the head offered only small advantage over a single rotation through 45°for detecting elevation differences. Veryslight rotation, as observed using a 0.5-sec signal, seemed sufficient to prevent front/back confusion. Cluster analysis showed that, in detecting elevation, some listeners ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 13 publications
8
106
2
1
Order By: Relevance
“…It was confirmed the front-back error rate in LPN (<1 kHz) was larger than those of other stimuli as mentioned in previous studies [2][3][4][5][6][7]. A statistical test suggested that head movement may reduce the front-back error rate effectively when the duration is long.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It was confirmed the front-back error rate in LPN (<1 kHz) was larger than those of other stimuli as mentioned in previous studies [2][3][4][5][6][7]. A statistical test suggested that head movement may reduce the front-back error rate effectively when the duration is long.…”
Section: Discussionsupporting
confidence: 61%
“…In particular, the front-back error, in which a sound with frontal incident is wrongly perceived as coming from behind, or vice versa, may be dramatically reduced by allowing head rotation [2][3][4][5][6][7]. Perrett and Noble [4] examined the effect of the duration of sound stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that head movements enable subjects to localize real sources more accurately (Perrett and Noble, 1997) and reduce the number of front-back confusions (Wightman and Kistler, 1999). Head movements have been shown to be useful in distance perception of virtual sources using Wave-Field Synthesis rendering (Rébillat et al, 2012).…”
Section: Head Trackingmentioning
confidence: 99%
“…Fixational eye movements are important for visual processes (Kelly, 1979;Tulunay-Keesey and VerHoeve, 1987;Rucci and Desbordes, 2003), head movements may assist in sound localization (Wallach, 1940;Perret and Noble, 1997;Wightman and Kistler, 1999), and hand movements improve tactile performance (Lamb, 1983;Gamzu and Ahissar, 2001). Movements of eyes and hands move stimuli across sensory receptors, thus enriching sensation with information unavailable when stimuli are fixed in place on the eye or hand (Ahissar and Arieli, 2001).…”
Section: Introductionmentioning
confidence: 99%